A natural heme‐signature variant of CYP267A1 from Sorangium cellulosum So ce56 executes diverse ω‐hydroxylation. (4th November 2014) - Khatri, Yogan; Hannemann, Frank; Girhard, Marco; Kappl, Reinhard; Hutter, Michael; Urlacher, Vlada B.; Bernhardt, Rita
<x xml:space="preserve">Abstract</x> A novel naturally occurring heme‐signature variant of CYP267A1 from myxobacterium Sorangium cellulosum So ce56 and its mutant L366F, the actual mimic of the 'conserved' heme‐signature of cytochromes P450, were heterologously expressed in Escherichia coli in a soluble form and purified. The UV–visible characteristics of both variants were highly similar. Although leucine replaced the phenylalanine in the heme‐signature domain of CYP267A1, EPR measurements of the ligand‐free wild‐type CYP267A1 and the mutant L366F showed low‐spin rhombic species suggesting a conserved heme environment of the P450s. The need of primary redox partners for the orphan P450 was sustained by the bovine redox system and a class‐I electron transfer path was provided during fatty acid hydroxylation. CYP267A1 showed higher activity and produced more diverse ω‐hydroxylated products compared with L366F. In both enzymes the regioselectivity of the fatty acid hydroxylation shifted towards the inner carbon atoms of the fatty acid chains with increasing carbon chain lengths. Our docking results in a homology model of the protein showed that longer fatty acids need to be folded to fit into the binding pocket. In the mutant L366F, the ω‐1 and ω‐2 positions which exhibit the largest electron density of the highest occupied molecular orbital are preferred. It is speculated that the leucine heme‐signature variant of P450 might have evolved under selective evolutionary pressure, which confers an increased advantage to generate a broader spectrum of related alcohols and carboxylic acids required for the bacterial homeostasis or metabolism in a particular ecological niche.